The Impact of Good Corporate Governance and Financial Technology Innovation on Indonesian Bank Financial Performance - Fachrurrozie; Ahmad Nurkhin; Hasan Mukhibad; Abdul Rohman; Christian Wiradendi Wolor (Jurnal Dinamika Akuntansi, 2024)
Purposes: This study intends to explore the influence of Good Corporate Governance (GCG) and financial technology innovation on the financial performance of the banking sector in Indonesia. The existence of the board of directors and board of commissioners measures GCG. The extent to which the digital services provided by banks to customers will measure financial technology innovation. Methods: This study intends to explore the influence of Good Corporate Governance (GCG) and financial technology innovation on the financial performance of the banking sector in Indonesia. The existence of the board of directors and board of commissioners measures GCG. The extent to which the digital services provided by banks to customers will measure financial technology innovation. Findings: The findings demonstrate that the composition of the independent board of commissioners can play a significant role in the financial performance of Indonesian banks, particularly in terms of Return on Assets (ROA) and Return on Equity (ROE). Financial technology innovation can determine ROE significantly, even in a negative direction. In addition, the size of the bank can determine ROA and ROE significantly and positively. The implications of the study show that the role of GCG mechanisms still has not had a significant impact on the financial performance of banks in Indonesia. Therefore, the role and function of GCG will be optimized for implementation. Likewise, financial technology innovation still cannot play a significant role in the short term. Novelty: The novel aspect of this study is the inclusion of financial technology innovation as a variable, which is crucial for banks to sustain performance during the pandemic and navigate the rapid advancements in financial technology. Banks must deliver quick and accurate services to their customers.